Pengaruh Phonophoresis Untuk Menurunkan Nyeri Pasien Osteoarthritis Lutut - Saifudin Zuhri (Poltekkes Kemenkes Surakarta, 2019)
Background: In everyday life activities human beings need prime conditions to create functional motion. One factor that interferes with functional motion is pain. The goal of physiotherapy for people with pain is to relieve pain. Many of the physiotherapy modalities recommended for reducing pain include phonophoresis. But the phonophoresis modality has not been widely implemented in Indonesia. Objective: To determine the effect of phonophoresis on reducing knee pain in patients with knee osteoarthritis. Methods: This study was a pure experiment with a pre-test and post-test with control group design. The study subjects were patients with knee osteoarthritis who met the inclusion and exclusion criteria. From the number of patients who came to the physiotherapy polyclinic of Dr Moewardi Hospital Surakarta, they would be randomized to the experimental group and the control group. The experimental group will get standard therapy at Dr Moewardi Hospital Surakarta plus phonophoresis, while the control group only gets standard therapy from the hospital. The independent variable is the administration of phonophoresis and the dependent variable is a decrease in knee pain. Statistical analysis using t-test. Results: Of Phonophoresis and standard therapy can reduce knee pain. More pain occurs in phonophoresis. Conclusion: Phonophoresis can be selected as a therapy to reduce pain in people with osteoarthritis